The Role of Village Government in Businesses Belonging to The Village - Akhyar Maulana; Setia Budhi; Tomi Oktavianor (Asean Study Center Lambung Mangkurat University, 2022)
This research uses qualitative research methods. This research was conducted in Serongga Village, Kelumpang Hilir District, Kotabaru Regency, South Kalimantan Province. Informants from the implementation of this study are apparatus of Serongga Village, operational executor of Bina Sejahtera Village-Owned Enterprises, as well as business observers in Serongga Village. Data collection uses observation, interview, and documentation techniques. Data analysis techniques using model interactive analysis. Result research shows that the Serongga Village Government is categorized as an active role, participatory role, and passive role inthe realm of developing Business Entity Owned by Bina Sejahtera Village, which includes aspects, namely: m emberi advice, advice and opinions, considerations, supervision, appointing and dismissing operational implementers, providing problem solving, and delivering financial analysis, activity plans and capital increase planning needs, assimilating developmen, protecting village businesses from political attacks, accommodate the aspirations of the people.